Ensuring the cybersecurity of ASU TP through the use of plasma technology - Толюпа, Сергій; Самохвалов, Юрій; Штаненко, С. (Київський національний університет імені Тараса Шевченка, 2021)
In modern conditions, cybersecurity issues are moving from the level of information protection at a separate object of computer technology to the level of creating a single cybersecurity system of the state, as part of the information and na tional security system responsible for protecting not only information in.the narrow sense, but also all cyberspace. In the process of forming global cyberspace, military and civilian computer technologies are converging, new means and methods of influencing the information infrastructure of a potential adversary are being developed, and specialized cyber centers are being created and implemented on high-tech platforms. At present, the cybersecurity procedure does not fully reflect the issues related to the cybersecurity of the ACS TP. This is due to the fact that the ACS PA was originally developed based on the ideology of physical isolation from external networks and strict delimitation of access by service personnel, using specific software, information exchange via industrial communication protocols Modbus, Profibus, etc., which often work on top of the TCP / IP protocol. Accordingly, there are many vulnerabilities in the ACS TP, the probability of which in various cyber incidents is directly proportional to the importance and significance of the object. Given the fact that the ACS TP have become an integral part of our existence, respectively, the problem of cybersecurity of the systems under consideration is today an urgent and timely task. The article discusses an approach to ensuring the cybersecurity of automated process control systems (APCS) by creating intelligent cybersecurity systems (ISCs). It is assumed that the construction of the proposed systems should be based on the concept of "evolution (development)", that is, the ability of the system to adapt through changes in parameters under the influence of external and internal cyber threats (cyber attacks), through the applied technologies, to counter cyber attacks throughout the entire life cycle. Technically, it is proposed to implement the ISCs by means of using an expert system and disaster-tolerant information systems (DIS), a characteristic feature of which, in contrast to fault-tolerant systems, is the continuation of work in conditions of massive and, possibly, consecutive failures of the system or its subsystems as a result of cyberattacks. These properties (catastrophic properties – system survivability) are possessed by programmed logic integrated circuits (FPGA) – a class of microprocessor systems, a characteristic feature of which is the ability to implement a multiprocessor (parallelized) structure that can withstand external influences (cyber attacks). By themselves, FPGA are an integrated circuit, the internal configuration of which is set by programming using special languages for describing hardware.

У сучасних умовах питання кібербезпеки переходять із рівня захисту інформації на окремому об’єкті обчи слювальної техніки на рівень створення єдиної системи кібербезпеки держави, як складової частини системи інформаційної та національної безпеки, що відповідає за захист не тільки інформації, у вузькому сенсі цього слова, а й усього кіберпростору. У процесі формування глобального кіберпростору відбувається конвергенція військових і цивільних комп’ютерних технологій, розробляються нові засоби і методи впливу на інформаційну інфраструктуру потенційного противника, створюються спеціалізовані кібернетичні центри, які реалізують ся на високотехнологічних платформах. Нині процедура кіберзахисту не в повному обсязі відображає питання, пов’язані з кібербезпекою автоматизованих систем управління технологічним процесом (АСУ ТП). Це пов’язано з тим, що АСУ ТП спочатку розроблялася з урахуванням ідеології фізичної ізоляції від зовнішніх ме реж і суворого розмежування доступу обслуговуючого персоналу, у цьому процесі застосовується специфічне програмне забезпечення, обмін інформацією здійснюється за промисловими комунікаційними протоколами Modbus, Profibus тощо, які часто працюють поверх TCP/IP протоколу. Відповідно в АСУ ТП виникає безліч вразливостей, імовірність використання яких у разі різних кіберінцидентів прямо пропорційна важливості і значимості об’єкта. З огляду на той факт, що АСУ ТП стали невід’ємною частиною нашого існування, відпо відно проблема кібербезпеки систем, які розглядаються, нині є актуальним і своєчасним завданням. У статті розглянуто підхід до забезпечення кібербезпеки АСУ ТП шляхом створення інтелектуальних систем кібербез пеки (ІСКб). Передбачено, що в основу побудови запропонованих систем повинно бути покладено поняття "еволюція (розвиток)", тобто здатність адаптації системи через зміну параметрів під впливом зовнішніх і внутрішніх кіберзагроз (кібератак), шляхом застосовування технологій із протидії кібератакам протягом усього життєвого циклу. Технічно реалізувати ІСКб запропоновано за рахунок застосування експертної сис теми і катастрофостійких інформаційних систем (КАІС) характерною особливістю яких, на відміну від від мовостійких систем, є продовження роботи в умовах масових і, можливо, послідовних відмов системи або її підсистем у результаті проведення кібератак. Такими властивостями (катастрофостійкими властивостями) володіють програмовані логічні інтегральні схеми (ПЛІС) – клас мікропроцесорних систем, характерною особ ливістю яких є можливість реалізації багатопроцесорної структури, здатної протидіяти зовнішнім впливам (кібератакам). Слід зазначити, що сучасні ПЛІС представляють собою інтегральну схему, внутрішню конфі гурацію якої задано шляхом програмування за рахунок застосування спеціальних мов опису апаратури.
Забезпечення кібербезпеки АСУ ТП шляхом застосування пліс-технології
Keywords: cybersecurity; automated control system; catastrophic system; programmable logic integrated circuit; expert system; кібербезпека; автоматизована система управління; катастрофостійка система; програована логічна інтегральна схема; експертна система